Etika Pasar dan Kejujuran Transaksi dalam Pasar Persaingan Sempurna: Perspektif Ekonomi Islam - Munjid, Mohamad Abdul; Sungkawaningrum, Fatmawati (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
This paper aims to explore the role of market ethics and honesty in transactions as important factors in achieving perfectly competitive markets, especially from an Islamic economics perspective. In the Islamic economic system, market ethics emphasize fairness, transparency and honesty in trading. A perfectly competitive market, characterized by a large number of sellers and buyers, perfect information, and freedom to enter and exit the market, is considered a fair mechanism for determining fair prices. Through a literature review, this paper highlights how the principles of market ethics and honest transactions contribute to market effectiveness as well as economic justice. Keywords: Market Ethics, Perfect Competition Market, Islamic Economics